Comparative study of physico-chemical analyses of different water resources in Setiu Wetland, Terengganu - Lani M.N.; Malek Rivan N.F.; Ismail A.; Wan Omar W.B.; Hassan Z.; Suhaili Z. (Springer International Publishing, 2024)
Indexed by SCOPUS